Coordination, Cooperation, and Conflict Between Caring Parents in Burying Beetles - Smiseth, Per T. (Frontiers in Ecology and Evolution, 2019)
Much of our current understanding of coordination, cooperation and conflict between male and female parents caring for their joint offspring derives from studies conducted on birds. However, biparental care is not unique to birds but has evolved repeatedly in a wide range of other taxa, including mammals, reptiles, amphibians, fishes, insects and crustaceans. Here I highlight how recent studies on burying beetles in the genus Nicrophorus provide new and complementary insights into biparental care to studies conducted on birds. Firstly, coordination between parents might be more complex than traditionally recognised, often involving multiple mechanisms such as negotiation and direct assessment of partner’s state. Secondly, coordination is not restricted to parental care, but extends to other interactions between caring parents such as interactions over food consumption from a shared resource. Finally, cooperation may have a stronger impact on coordination between parents than has been traditionally recognised. I suggest that, in order to expand our understanding of coordination, cooperation and conflict between male and female parents, we now need to extend empirical work to a wider range of taxa, develop new experimental designs for detecting alternative mechanisms of coordination, and use of multiple experimental designs in all taxa.